2014
DOI: 10.1002/piq.21157
|View full text |Cite
|
Sign up to set email alerts
|

Sales Teams or Salespersons: Performance Implications for Embracing Individualistic and Collectivistic Cultural Values in a Global Marketplace

Abstract: Th e development of pragmatic predictors of sales force performance typically focuses on factors such as extrinsic and intrinsic motivation, performancebased compensation, selection and training procedures, personality characteristics such as extroversion, and job satisfaction (Baldauf, Cravens, & Piercy, 2001;Frino, 2010). DeCarlo, Rody, and DeCarlo (1999) concluded that "incorporating culture as a moderating factor into global models of management practices allows easier prediction of expected behaviors in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Ross et al (2014) compared two individualistic countries (Australia and the United States) with two collectivistic countries (Japan and South Korea) on WFC. They expected collectivists to experience more WFC than individualists, yet they found that individualists experienced more WFC than collectivists.…”
mentioning
confidence: 99%
“…Ross et al (2014) compared two individualistic countries (Australia and the United States) with two collectivistic countries (Japan and South Korea) on WFC. They expected collectivists to experience more WFC than individualists, yet they found that individualists experienced more WFC than collectivists.…”
mentioning
confidence: 99%